2010
DOI: 10.1289/ehp.0901661
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles Induce Changes of the Electrical Activity of Neuronal Networks on Microelectrode Array Neurochips

Abstract: BackgroundNanomaterials are extensively used in industry and daily life, but little is known about possible health effects. An intensified research regarding toxicity of nanomaterials is urgently needed. Several studies have demonstrated that nanoparticles (NPs; diameter < 100 nm) can be transported to the central nervous system; however, interference of NPs with the electrical activity of neurons has not yet been shown.Objectives/methodsWe investigated the acute electrophysiological effects of carbon black (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
69
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(70 citation statements)
references
References 41 publications
0
69
1
Order By: Relevance
“…Nasal mucosa cells Cytotoxic, genotoxic and pro-inflammatory effects [77] Hepatocytes Inflammatory and genotoxic effects [56] Renal cells Cytotoxicity [78] Neurons Neurotoxic effect by disturbing the electrical activity of neuronal networks [7] Lung epithelial cells Cytotoxicity [79] Carbon black nanoparticles (CB-NPs) Lymphocytes Induction of chromosomal aberrations [80] Hepatocytes Hepatotoxicity [81] Neurons Dopaminergic neurons damage pathways [82] Lung epithelial cells Toxicity and inflammatory response. [83] Lymphocytes Cytotoxicity and genotoxicity [84] Silica nanoparticles (SiO 2 ) Fibroblast Cytotoxicity [25] Hepatocytes Genotoxicity, carcinogenicity, hepatotoxicity and inflammation [48,85] Renal cells Induction of oxidative stress and cytotoxicity [86] Neurons Neurotoxicity [7] Lung epithelial cells Genotoxicity, mutagenicity and carcinogenicity [87,88] Lymphocytes Induction of oxidative stress and reduction of immune capacity, Genotoxicity [27,80] Titanium dioxide nanoparticles (TiO 2 )…”
Section: Hepatocytesmentioning
confidence: 99%
See 2 more Smart Citations
“…Nasal mucosa cells Cytotoxic, genotoxic and pro-inflammatory effects [77] Hepatocytes Inflammatory and genotoxic effects [56] Renal cells Cytotoxicity [78] Neurons Neurotoxic effect by disturbing the electrical activity of neuronal networks [7] Lung epithelial cells Cytotoxicity [79] Carbon black nanoparticles (CB-NPs) Lymphocytes Induction of chromosomal aberrations [80] Hepatocytes Hepatotoxicity [81] Neurons Dopaminergic neurons damage pathways [82] Lung epithelial cells Toxicity and inflammatory response. [83] Lymphocytes Cytotoxicity and genotoxicity [84] Silica nanoparticles (SiO 2 ) Fibroblast Cytotoxicity [25] Hepatocytes Genotoxicity, carcinogenicity, hepatotoxicity and inflammation [48,85] Renal cells Induction of oxidative stress and cytotoxicity [86] Neurons Neurotoxicity [7] Lung epithelial cells Genotoxicity, mutagenicity and carcinogenicity [87,88] Lymphocytes Induction of oxidative stress and reduction of immune capacity, Genotoxicity [27,80] Titanium dioxide nanoparticles (TiO 2 )…”
Section: Hepatocytesmentioning
confidence: 99%
“…[83] Lymphocytes Cytotoxicity and genotoxicity [84] Silica nanoparticles (SiO 2 ) Fibroblast Cytotoxicity [25] Hepatocytes Genotoxicity, carcinogenicity, hepatotoxicity and inflammation [48,85] Renal cells Induction of oxidative stress and cytotoxicity [86] Neurons Neurotoxicity [7] Lung epithelial cells Genotoxicity, mutagenicity and carcinogenicity [87,88] Lymphocytes Induction of oxidative stress and reduction of immune capacity, Genotoxicity [27,80] Titanium dioxide nanoparticles (TiO 2 )…”
Section: Hepatocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…Nasal exposure of airborne nano-ZnO or nano-TiO 2 in rodents results in their translocations into the brain (Kao et al, 2012b;Wang et al, 2008), and several groups have reported the effects of these nanomaterials on neuronal viability or neuronal excitability in vitro (Gramowski et al, 2010;Valdiglesias et al, 2013aValdiglesias et al, , 2013bLiu et al, 2010;Long et al, 2007;Jeng and Swanson, 2006). However, it is still unclear whether these nanomaterials affect the differentiation and development of neurons.…”
Section: Introductionmentioning
confidence: 99%
“…6 During the past several years, there have been numerous toxicological investigations of airborne NPs and their impact on occupational health and the environment. [7][8][9] Experimental models have provided clear evidence that NPs can not only translocate to organs after inhalation, [10][11][12] but can also cause disruption of the blood-brain barrier through different administration routes, including the intravenous, the intraperitoneal, and the intracerebral route. 13,14 Inhaled NPs either translocate directly into the brain or exit the lungs and enter the circulation as shown in rat experiments.…”
Section: Introductionmentioning
confidence: 99%